Liver dysfunction in geriatric patients - Kasper, Philipp; Tacke, Frank; Heppner, Hans Jürgen; Michels, Guido (Die Gastroenterologie, 2023)
With increasing age in addition to alterations of the cardiovascular, neurocognitive and musculoskeletal systems, alterations also occur in hepatic organ function. As a result of morphological and functional age-related processes, progressive hepatic organ dysfunction can develop with increased vulnerability with respect to endogenous and exogenous noxious substances and impaired hepatic regenerative capacity. Frequent causes of liver dysfunction in the geriatric population include non-alcoholic fatty liver disease (NAFLD), alcoholic liver disease, viral hepatitis, autoimmune hepatitis and drug-induced liver injury. The prompt initiation of adequate diagnostic measures for identification of the underlying etiology is important for timely initiation of appropriate treatment and to reduce the risk of progressive impairment of hepatic function and associated complications.
CRIS-Team WoS Importer:2023-03-31